A Black Feminist Analysis of Patient Provider Concordance in Sexual Health Care. Issue 2 (April 2023) - Wade, Jeannette; Frederick, Helyne; Parker, Sharon; Wiley, Briana; Dillon, Hannah; Wilson, Dorrian; Taylor, Kwani
Racial disparities in gynecological health have persisted over time. Interestingly, there is a dearth of research that centers Black women's experiences with gynecologists and even less research that uses Black feminist theory and methods. We use semi-structured interviews ( N = 39) to understand the sexual health care related experiences of Black women at a Predominately White Institution (PWI) and a Historically Black College or University (HBCU). We found that the following themes captured Black women's experiences: (1) Feeling Ignored, (2) Having Their Intelligence Insulted, (3) Receiving Proper Help and Education, (4) Benefits of Concordance across Race and Sex Categories, (5) Discomfort Due to Sexual Taboos, (6) Perceived Medical Racism, (7) Impact of other Intersectional Identities, and (8) No Impact. Implications for enhancing experiences with sexual health care appointments and improving patient provider relationships are discussed.